THE ROLE OF LEADERSHIP IN OVERCOMING EMPLOYEE WORK CONFLICT AT UD. PERKASA TANI - Odaligoziduhu Halawa (LPPM YPITI, 2026)
This study aims to determine the analysis of the role of leadership in resolving employee work conflicts at UD. Perkasa Tani, located in Gido District, Nias Regency. The research method used is a qualitative descriptive method, namely research that describes narratively based on research data that is objectively reviewed from interviews and observations. In this study, it resulted that the leadership role applied in resolving employee work conflicts at UD. Perkasa Tani is a democratic leadership style, in decision making the leader prioritizes group discussions, the leader respects the opinion of each employee. While the factors that cause employee work conflicts at UD. Perkasa Tani are, less than optimal division of tasks, differences of opinion between employees, sometimes poor communication between employees and feelings of being treated less fairly in appreciating the work of each employee.